Rizal and Republican Spain and other Rizalist essays: commemorative publication on the centenary of the martyrdom of Dr. José Rizal - Sarkisyanz, Emanuel (National Historical Institute, 1995)
The author analyzes the interplay between two opposing historical forces at work - liberalism versus traditionalism - in the 19th century Spain and the interaction between two Spains - Rizal's Spain and Rizal's Spanish Philippines. The study calls not only for a re-thinking of Jose Rizal and his political ideas, but also for a re-interpretation of Philippine history in the light of the continuity of the "democratic Republican" tradition in Spain since 1812. (DÜI-Alb)